2009
DOI: 10.1111/j.1744-7348.2008.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of genetically modified crops in light of future environmental and legislative challenges to the agri‐environment

Abstract: A key challenge for countries like Ireland up to 2030 is to produce sufficient supplies of food, feed and fuel, without compromising on public health or negatively impacting the environment. As we progress through the technology era,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Fourth, adherence to technology generates more willingness to buy products that make environmental and ethical claims. This finding could be explained by the idea that advanced food technologies could maximize production while minimizing environmental impact (O'Brien and Mullins, 2009), reducing the use of pesticides (Phipps and Park, 2002) and improving human well-being in developing countries (e.g. Anderson and Jackson, 2005;Bett et al, 2010).…”
Section: Social Representation Dimensions and Product Claimsmentioning
confidence: 99%
“…Fourth, adherence to technology generates more willingness to buy products that make environmental and ethical claims. This finding could be explained by the idea that advanced food technologies could maximize production while minimizing environmental impact (O'Brien and Mullins, 2009), reducing the use of pesticides (Phipps and Park, 2002) and improving human well-being in developing countries (e.g. Anderson and Jackson, 2005;Bett et al, 2010).…”
Section: Social Representation Dimensions and Product Claimsmentioning
confidence: 99%
“…Research into genetically engineering crops to improve their N use efficiency is ongoing (46). Recent papers have shown that, with the same amount of N fertilizer, certain genetically engineered crops could increase yields by over 30% compared with traditional crops (47).…”
Section: Recommended Behavioral Practices Include (More Details In Simentioning
confidence: 99%
“…However, concerns are being raised about the possible environmental impact of this technology. Yet, few studies have conducted a critical needs analysis to assess the potential of specific GM traits in light of issues, such as climate change, increased environmental legislation (e.g., EU Water Framework, Nitrates Directive, proposed reform to the Pesticide Directive and Common Agricultural Policy reform), mitigating biodiversity loss, and sustainable biofuel production [81].…”
Section: Herbicide-tolerant Crops and Evolution Of Super Weedsmentioning
confidence: 99%